Innovation of Sustainable and Greener Raised Median or Road Divider on Expressway - Ambak, Kamarudin; Abdul Rahim, Norfatehah; Rosli, Naida (International Journal of Sustainable Construction Engineering and Technology, 2020)
The development of road construction in Malaysia was showed a good growth with the use of hi-tech equipment. However, it’s failed to prevent the impact of accidents occur when involving the road furniture especially road barrier. This study purpose a new innovation design for the construction of road divider that more sustainable and greener which is eco-friendly. This study was conducted to modify the material used on the road divider, so that the suitability of the material can reduce the impact of the vehicle during road accident. Objective of this study is to test and design greener sustainable materials as a road median component. Besides, this study is to determine the suitability and characteristics of materials for road median. Materials used in this study are gunny sacks filled with sand, laterite soil, soft turfing (cow and pearl grass) and used tire as a cushion effect. Based on experiment testing, sieve analysis result showed that river sand is a good grade sand and suitable for road median. While, direct shear test showed sand and soil used for this study are suitable because there have a high shear strength. For grass observation, cow grass is suitable compare pearl grass in term of growth rate, maintenance cost, durability on sunlight exposure and weather in Malaysia. The load applied for conducting impact test on the sand sack were 14.08N 25.6N 44.8N. The initial damage occurred when a force reaches at 44.8N. However, the condition of the arrangement of sand sack is still stable. In conclusion, this new innovation of green and sustainable road divider has high potential in absorbing the impact of accidents.